DETERMINATION OF THE ACCOUNTING SUBSTANCE OF COSTS AND THEIR CLASSIFICATION - BONDARENKO, Natalya (Herald of Khmelnytskyi National University. Economic sciences, 2023)
Enterprise costs have always been an important economic category, which characterizes the results of the enterprise and its profitability. The key condition for the organization of an effective management system is the reliability, completeness and promptness of the available information, about the costs, lost during the management process. This data is received by the management staff thanks to cost accounting, which is the central subsystem in the informational accounting system. The purpose of the article is to research and generalize the essence of costs and criteria for their classification, determination of the location of costs in the accounting system, and of enterprise management in modern economic conditions of development. The analysis of normative legal and scientific sources regarding aspect of the interpretation of the accounting and economic category "expenditure" testifies to it versatility and complexity. If in international and domestic regulatory documents, costs in most cases are interpreted as reduction of economic benefits, then in the scientific literature they are considered with three positions - financial, resource and accounting. In our opinion, it is appropriate to combine economic and accounting approach and to give the following definition to the researched category: costs are cost assessment of the resources consumed by the enterprise in the process of achievement certain defined purposes, the use of which leads to a reduction assets or an increase in liabilities, resulting in a decrease in equity capital (except in cases of its withdrawal or distribution by the owners). In the process of research, the controversial question was established distinguishing costs and expenses, as some scientists consider them synonyms, and the other emphasizes the essential differences between them. It was found that an effective system of organizing information about costs provides the ability to determine the peculiarities of the formation and distribution of costs for certain objects of management. The main classification features for distinguish types of expenses and group them depending on the detail of the information, which they transmit.